Nitric oxide inhibits hypoxia‐induced impairment of human RBC deformability through reducing the cross‐linking of membrane protein band 3. Issue 1 (14th September 2018) - Zhao, Yajin; Wang, Xiang; Wang, Ruofeng; Chen, Dong; Noviana, Milody; Zhu, Hongliang
Abstract: Aim: Nitric oxide (NO) prevents the decline of RBC deformability under high altitude and other ischemic and hypoxic conditions, but the clear mechanisms remain unknown. Here, we have carried out a systematic study to find the mechanisms of NO‐induced regulation of RBC deformability under hypoxia. Methods: NO levels, RBCs membrane elongation index (EI), membrane protein band 3 methemoglobin (MetHb) were determined during hypoxia (0 to 120 minutes). To validate the role of NO in regulating RBC deformability, tests were also performed with a NO donor (sodium nitroprusside) or a NO synthase inhibitor (l ‐nitro‐arginine methylester) under 60 minutes hypoxia. Results: Hypoxia for 45 minutes increased NO levels from 25.65 ± 1.95 to 35.26 ± 2.01 μmol/L, and there was a plateau after 60 minutes hypoxia. The EI did not change before 45 minutes hypoxia, but decreased from 0.567 ± 0.019 to 0.409 ± 0.042 (30 Pa) after 60 minutes hypoxia. The cross‐linking of band 3 and phosphotyrosine increased after 45 minutes hypoxia. All can be alleviated by supplement NO and aggregated by inhibiting NOS. However, the MetHb was not present this trend. Conclusion: NO may prevent decreased of RBCs deformability through reducing the cross‐linking of membrane band 3 under hypoxia; this helps microvascular perfusion of RBCs during ischemic and hypoxic disease states. Abstract : In this study, we evaluated the association of nitric oxide and RBCs deformability under hypoxia. We demonstrated here that hypoxia‐induced nitric oxide is closely related with the maintenance of RBCs deformability under hypoxia, and also this study provides a potential molecular mechanism of NO regulates RBCs deformability under hypoxia.